2017
DOI: 10.1177/1540796917697311
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions About Expert Teaching for Students With Severe Disabilities Among Teachers Identified as Experts

Abstract: Teaching students with severe disabilities is a complex endeavor, and the skills and qualities of expert teachers for students with severe disabilities are not well understood. A lack of understanding about the unique roles and expertise of teachers of students with severe disabilities can influence the quality of education students with severe disabilities receive and can also affect teacher preparation, development, and evaluation. In this qualitative study, the authors interviewed 11 teachers of students wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Teacher educators in this study used innovative approaches to build and sustain relationships with professionals in the field, including hosting social and networking opportunities (e.g., Community of Practice and Social Hour). These relationships also served as a way to help address the isolation many teachers of students with significant disabilities feel (Greenway et al, 2013; Ruppar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Teacher educators in this study used innovative approaches to build and sustain relationships with professionals in the field, including hosting social and networking opportunities (e.g., Community of Practice and Social Hour). These relationships also served as a way to help address the isolation many teachers of students with significant disabilities feel (Greenway et al, 2013; Ruppar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This ability to continually advocate for students and act as a change agent has also been identified as an indicator of expertise of teachers of students with significant disabilities (Ruppar, Roberts, & Olson, 2015, 2017) and is an essential disposition for preservice teachers to gain during their teacher preparation. Teacher educators need to prepare preservice teachers who are ready to negotiate these challenges while actively problem solving to promote change (Ashby, 2012; Cameron & Cook, 2007; Copeland et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the first phase of the study, we examined faculty perceptions (Ruppar et al, 2015). In the second phase, we examined teacher perceptions (Ruppar et al, 2017). In the current article, we examine administrator perceptions of high-quality instruction.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, previous research on teachers of students with severe disabilities has reported that teachers perceive their administrators as “afraid to step in their classroom” and report that administrators often defer to them as the “experts” because they lack an understanding of appropriate instructional practices (Greenway et al, 2013, p. 462). This is concerning considering that students with severe disabilities are a historically marginalized group and their teachers often express feeling isolated and misunderstood by others in their school context (Greenway et al, 2013; Ruppar, Roberts, & Olson, 2017).…”
Section: Vision Of Instruction For Students With Severe Disabilitiesmentioning
confidence: 99%